Age-dependent association of KIBRA genetic variation and Alzheimer's disease risk - Rodríguez-Rodríguez, Eloy; Infante, Jon; Llorca, Javier; Mateo, Ignacio; Sánchez-Quintana, Coro; García-Gorostiaga, Inés; Sánchez-Juan, Pascual; Berciano, José; Combarros, Onofre (Neurobiology of aging, 2009)
An association between memory performance in healthy young, middle aged an elderly subjects and variability in the KIBRA gene (rs17070145) has been recently described. We analyzed this polymorphism in 391 sporadic Alzheimer's disease (AD) patients and 428 cognitively normal control subjects. The current study reveals that KIBRA (rs17070145) T allele (CT and TT genotypes) is associated with an increased risk (OR 2.89; p=0.03) for very-late-onset (after the age of 86 years) AD.